If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2h + -1) = 5 Reorder the terms: 4(-1 + 2h) = 5 (-1 * 4 + 2h * 4) = 5 (-4 + 8h) = 5 Solving -4 + 8h = 5 Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 8h = 5 + 4 Combine like terms: -4 + 4 = 0 0 + 8h = 5 + 4 8h = 5 + 4 Combine like terms: 5 + 4 = 9 8h = 9 Divide each side by '8'. h = 1.125 Simplifying h = 1.125
| -2(4b+1)+(9b-8)=0 | | y=x^2-6x+1 | | 1.2q-2.6-2.2q=-2.0q-3.4 | | x=2+8 | | 4(x+2)=2(x+8) | | -3y+3=-4y+8 | | 8k^2-40k=0 | | 3n^2+33n+72=0 | | x+1/6=-2/3 | | 13x+7=2x-9 | | t-15=-48 | | 5u=14u+3 | | 7x+y=21y | | 3(x+5)-8(x-3)=20 | | 6x^2+3x=5 | | 7-x=9+3x | | 4x-14=2x+8 | | -3(-9w+6)-6w=3(w-8)-2 | | -5(x+1)=5x-7+2(4x+4) | | 45=52-x | | 1+5(2x-1)=-2(5x-4)+2x | | 37=9+x | | -3(3w-2)+4w=3(w+4) | | 40-x=29 | | .10x=130 | | -3(-8u+3)-4u=2(u-8)-7 | | (x+4)(x-2)=5x | | y=13x-18 | | 3x^2+4x=15 | | 12x^2-x-1=0 | | -3t+9=13-7t | | -5x+9y=21 |